Cardiomegaly of the larger twin in monochorionic twin pregnancies warrants neonatal intensive care even without twin-to-twin transfusion syndrome. (October 2019) - Iwagaki, Shigenori; Takahashi, Yuichiro; Chiaki, Rika; Asai, Kazuhiko; Matsui, Masako; Katsura, Daisuke; Yasumi, Shunsuke; Furuhashi, Madoka
Abstract: Objectives: Some monochorionic twin pregnancies need intensive cardiac management even in the absence of twin-to-twin transfusion syndrome after birth. The purpose of this study was to investigate risk factors related to persistent hypotension requiring cardiotonic agent use among monochorionic twin pregnancies without twin-to-twin transfusion syndrome. Study design: This was a retrospective study of 316 monochorionic twin pregnancies without twin-to-twin transfusion syndrome (632 babies). All cases were treated in the neonatal intensive care unit. Hypotension was defined as mean arterial blood pressure below the norm for gestational age. Decreased left ventricular ejection fraction was defined as a value <60%. Dopamine, dobutamine and phosphodiesterase III inhibitor were used as cardiotonic agents for hypotension persisting even after adequate infusion. Results: Among the 632 cases, 33 (5.2%) needed cardiotonic agents for persistent hypotension. The frequency of persistent hypotension with decreased left ventricular ejection fraction was significantly higher among larger twins (4.4%) than among smaller twins (0.6%, p = 0.0038). In larger twins, multivariate analysis showed that Z-score for cardiothoracic area ratio (odds ratio, 2.31; p < 0.001), tricuspid regurgitation (odds ratio, 6.34; p = 0.015) and gestational age at delivery (odds ratio, 0.66; p < 0.001) correlated with persistent hypotension. In smaller twins, univariate analysis showed gestational age at delivery, birth weight, Z-score for birth weight and Z-score for cardiothoracic area ratio of the larger twin were related to persistent hypotension. Concentration of brain natriuretic peptide in the umbilical vein in larger and smaller twins were significantly correlated (coefficient of correlation = 0.792, p < 0.001). Conclusions: In monochorionic twin pregnancies, attention needs to be given to cardiac size along with amniotic fluid and fetal growth. Both larger and smaller twins carry risks of persistent hypotension after birth. Close observation is needed, especially in cases where the larger twin displays cardiomegaly despite absence of twin-to-twin transfusion syndrome.